2016
DOI: 10.1007/s11010-016-2663-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 promotes lung cancer cell proliferation and migration via the IL-22R1/STAT3 and IL-22R1/AKT signaling pathways

Abstract: Lung cancer continues to be an enormous burden on current health care systems throughout the world, with more than a million deaths every year. Previous studies have shown that interleukin-22 (IL-22) promotes survival and resistance to chemotherapy in human lung cancer cells. However, the association of IL-22 expression with recurrence of lung cancer is still unclear. In this study, we found that expression of IL-22 was upregulated in tumor tissues and serum from patients with recurrent non-small cell lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Lung cancer cell lines also exhibited enhanced invasive capacity and survival, which was linked to higher activation of STAT3 and AKT. Knockdown of IL22Ra1 abolished this survival advantage . Genetic linkage analysis found SNPs in the IL22 locus that correlated with NSCLC.…”
Section: Il‐22 and Cancermentioning
confidence: 94%
“…Lung cancer cell lines also exhibited enhanced invasive capacity and survival, which was linked to higher activation of STAT3 and AKT. Knockdown of IL22Ra1 abolished this survival advantage . Genetic linkage analysis found SNPs in the IL22 locus that correlated with NSCLC.…”
Section: Il‐22 and Cancermentioning
confidence: 94%
“…Among these, the percentage of T helper 17 (Th17) cells and related cytokine interleukin 17 (IL-17) were increased in patients with extensive tumor invasion [57][58][59]. In addition, another cytokine IL-22, produced by Th17 cells, enhanced the migration and invasion in NSCLC cell lines [60]. These results suggest that Th17 cells may be significantly correlated with the invasive potential of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…IL-22 itself has been shown to promote cellular proliferation in NSCLC cell lines [70], and indeed confirmation that IL-22 was both upregulated and pro-proliferative in NSCLC came from a recent study which demonstrated that the proliferative response was driven through the Il-22R1 receptor via either STAT3 or AKT signalling [73]. We and others, have also demonstrated that IL-22R1 was overexpressed in NSCLC [42,43], and analysis of IL-22R1expression in n=1,926 patients linked high expression of the receptor to poor prognosis [43].…”
Section: Activated T Cells Including T Helper 22 (Th22) Cells Th17 mentioning
confidence: 89%